2012
DOI: 10.1111/zph.12009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Sampling Strategies and Laboratory Methods for the Detection of C. jejuni and C. coli from Broiler Flocks at Primary Production

Abstract: The objective of the study was to evaluate the performance of different combinations of sample type, transport medium and culture methods for the recovery of Campylobacter jejuni and C. coli from broiler flocks at primary production. Boot swabs moistened with one of four different transport media [maximum recovery diluent (n=120), Exeter broth (EX) (n=120), buffered peptone water (n=120) and modified semi-solid Cary-Blair (n=120)], caecal samples (n=40) and faecal samples (n=120) from 40 broiler flocks were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 50 publications
3
25
1
3
Order By: Relevance
“…However, there is not yet an accepted standard method for the detection and isolation of Campylobacter spp. at farm level (Vidal et al, 2013). In commercial broiler chickens, Campylobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is not yet an accepted standard method for the detection and isolation of Campylobacter spp. at farm level (Vidal et al, 2013). In commercial broiler chickens, Campylobacter spp.…”
Section: Resultsmentioning
confidence: 99%
“…The use of boot swabs moistened in transport media can be an efficient alternative to caecal or faecal sampling at the farm (Vidal et al, 2013). This kind of sample has shown a good sensitivity and can be a good method for an early PCR detection of a Campylobacterpositive flock, for monitoring purposes.…”
Section: Resultsmentioning
confidence: 99%
“…This includes gaining insight into the dynamics of infection in broiler farms. There are few studies that have compared the suitability of different types of sample for the detection of Campylobacter at the slaughterhouse (Ugarte-Ruiz et al, 2012), or the performance of sampling methods on the farm (Vidal et al, 2013). As a first step to conduct studies of Campylobacter dynamics at farm level, we evaluated the sensitivity of two types of sample (caecal contents and cloacal swabs) in order to choose the most suitable one for the early detection of Campylobacter when culture methods are used.…”
Section: Introductionmentioning
confidence: 99%
“…These authors conclude that the enrichment method used affects both the number and species of Campylobacter isolated from naturally contaminated samples. In a separate study, Vidal et al (2013) found that enrichment in Exeter broth significantly increased the sensitivity of swab and cecal samples for the detection of Campylobacter spp. in broiler flocks.…”
Section: Isolation Enrichment and Maintenancementioning
confidence: 96%